2013
DOI: 10.1021/nl4008198
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsic Role of Nanoconfinement in Chemical Equilibrium: Evidence from DNA Hybridization

Abstract: Recently we predicted that when a reaction involving a small number of molecules occurs in a nanometric-scale domain entirely segregated from the surrounding media, the nanoconfinement can shift the position of equilibrium toward products via reactant-product reduced mixing. In this Letter, we demonstrate how most-recently reported single-molecule fluorescence measurements of partial hybridization of ssDNA confined within nanofabricated chambers provide the first experimental confirmation of this entropic nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 10 publications
4
42
0
Order By: Relevance
“…In the past, molecular dynamics simulations have suggested that confinement favors the bound state of short DNA oligomers because it increases the relative free energy of denatured oligomers, while simultaneously decreasing the free energy barrier of renaturation . Other forces, such as reduced entropy of mixing, may impact DNA affinity kinetics, resulting in a decrease in k off with confinement .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, molecular dynamics simulations have suggested that confinement favors the bound state of short DNA oligomers because it increases the relative free energy of denatured oligomers, while simultaneously decreasing the free energy barrier of renaturation . Other forces, such as reduced entropy of mixing, may impact DNA affinity kinetics, resulting in a decrease in k off with confinement .…”
Section: Resultsmentioning
confidence: 99%
“…Rubonovich et al. performed further analysis on the experiments of Shon et al., and suggested the results represent a nanoconfinement entropic effect on chemical equilibrium ‐ stabilizing the reaction products and reducing k off . In addition, Galvin et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the synergistic effects arising from the cooperation between the sites of different chemical nature discussed in the previous sections, the presence of multiple sites of the same nature inside the molecular‐sized zeolite pores can be crucial for the reactivity and catalytic properties of zeolites. The high density of the active sites in a confined space allows forming multiple interactions with the reactant molecules that define their specific orientation in space, which, in turn, may facilitate and direct their transformations along the predefined paths . This closely resembles the molecular recognition mechanism used by many enzymes and supramolecular catalysts to selectively activate substrates.…”
Section: Confinement‐induced Reactivity and Molecular Recognition Phementioning
confidence: 96%
“…For instance, theoretical works based on statistical arguments 13,14 have coined the term “nanoconfinement entropic effects” to describe the way in which chemical equilibrium is affected when considering only a small amount of molecules, observing a considerable shift w.r.t. the equilibrium in the macroscopic limit originating in the reduction in number of reactant–product mixed microstates.…”
Section: Introductionmentioning
confidence: 99%